El espacio geopolítico gaditano en época púnica. Revisión y puesta al día del concepto de «Círculo del Estrecho» - Niveau de Villedary y Mariñas, Ana M.ª (Gerión. Revista de Historia Antigua, 2001)
The main purpose of the present paper is to define, culturally and spatially, the underlying concept under the expression «Circle of the Straight». This term, very successful since it was coined by Tarradell in the sixties, has been used by researchers to refer to the area of economic and political influence of Gadir following the fall of Tiro. However, its characteristics have been hardly specified with accuracy, its genesis has not been clerified and it has never been linked to the rest of the Mediterranean cultural areas at that time, in the interest of achieving a more exact explanation of the political events of the period. Our aim is to outline the process that led to the formation of this geopolitical reality, wich always kept a marked Phoenician-oriental character. Secondly, we would like to specify those elements reflecting the economical activities of this zone —fishing products transformation and marketing on a large scale— which we believe delimit to a great extent the area we must include in our study and which constitute the factors that coordinate the territory politically and administratively. Lasty, through the analysis of these realities we will explain the political evolution followed by Gadir in the course of the Second Punic War.